Does drug consumption has an influence on plasmids diffusion in CZA-resistant Klebsiella pneumoniae isolates? - Federica Sacco; Luisa Torrini; Fabiana Diaco; Agnese Viscido; Guido Antonelli; Gianmarco Raponi (Microbiologia Medica)
Not available.